(untitled) (Indian Journal of Child Health, 2018)
Objective: The objective of the study was to evaluate the adverse effects of phototherapy both total and ionic calcium levels in neonates. Methods: A case–control prospective study was conducted in the Department of Pediatrics, over a period of 15 months. All neonates preterm or term with icterus in phototherapy range formed the study group(s). Serum calcium total and ionized were measured on a serial basis. Results: Neonates in the study group had significant fall in total serum calcium after phototherapy (0.94±0.49 mg/dl). Similarly, ionized serum calcium also decreased after phototherapy in study group (0.56±0.36 mg/dl), p<0.001 statistically significant. The overall incidence of hypocalcemia was 9.6%, higher in preterm (11.7%) than term (8.5%) neonates. Jitteriness and irritability both were seen in 25% of the neonates. None of the neonate had convulsion, but it may occur if the level falls further. Conclusions: While giving phototherapy to a premature baby or a sick baby we should monitor serum calcium levels. Prophylactically oral supplementation of calcium may be considered in newborns receiving phototherapy as it induces hypocalcemia.